Green public responsibility through environmental action and communication synergy: How agroforestry and mangrove synergy can make climate change messages stronger - Ari Kurnia; Diki Surya Irawan; Suharyanti Suharyanti; Aura Rizqia Tiffany (Journal of Community Service and Empowerment, 2025)
We need new and better ways for Environmental Community to talk to each other to deal with climate change. This Community Service project shows how Agroforestry and Mangrove Conservation can work together to make the message of climate change stronger through Green Public Communication. This is happening in Taiwan and Indonesia. This program is part of the University Social Responsibility (USR) program in Taiwan, and Tzu Chi University works with the program. First, the event's goal was to raise awareness about the environment by having volunteers clean up in Ximen, Taipei. Participants worked together to clean up public spaces, pick up trash, and spread the word about how important it is to keep the city clean and protect the environment. Second, this activity is all about the Agroforestry area, with a tour at the Tzu Chi University Agroforestry Area in Hualien. Third, there was a seminar and workshop in Jakarta for documentary filmmakers that taught them how to make digital campaign content about the environment for social media to make the message of climate change stronger. The goal of this program is to get more people involved in protecting mangrove ecosystems and agroforestry to fight climate change. The results show that working together across sectors and using Environmental Action methods and Digital Campaigns to spread public education messages through Social Media posts can make the climate change message stronger in society and get more people involved in protecting the environment.